The Increasing Penalty to Occupation-Education Mismatch - Hugh Cassidy; Amanda Gaulke (Institute of Labor Economics (IZA), 2023)
College-educated workers in jobs unrelated to their degree generally receive lower wages compared to well-matched workers. Our analysis of data from the National Survey of College Graduates shows that although the rate of this mismatch declined only slightly (19% to 17%), the wage penalty increased by 51% between 1993 and 2019. Changes in the composition of field of study over time, as well as declining returns to "excess" education above what is required for the occupation both help to explain the increasing penalty, especially for women. Mismatch has become more closely associated with lowerreturn occupations for men but not women.
Keywords: J24; I26; I23; J31; 330; education mismatch; field of study; wage penalty